MODELING PEDESTRIAN FLOWS TAKING INTO ACCOUNT HUMAN COMFORT LEVELS - Chernyshova, Oksana; Stepanchuk, Oleksandr; Dubyk, Oleksandr (Theory and practice of design, 2025)
The article discusses the issue of ensuring the comfort level of pedestrians in buildings using the example of railway stations. The authors examine the relationship between the geometric parameters of space, the characteristics of pedestrian flows, and individual perception of the environment. Particular attention is paid to assessing traffic conditions in crowded places, where comfort is influenced not only by the parameters of the premises, but also by psychophysiological factors of safety and convenience. An analysis of domestic and foreign research by scientists has made it possible to summarize modern approaches to assessing the level of comfort by introducing the concept of a comfort index. The results obtained will make it possible to ensure a more comfortable, safe, and barrier-free environment in station complexes for passengers of all categories. The purpose of the work is to create a quantitative model for assessing pedestrian comfort, taking into account the relationship between the physical parameters of the environment and users’ perception of comfort. Methodology. The research methods are based on a systematic approach to analyzing pedestrian traffic conditions in buildings, using railway station complexes as an example. A comprehensive combination of quantitative and qualitative indicators is used to assess comfort. The proposed comfort index is based on criteria that take into account spatial parameters, flow characteristics, and individual behavioral characteristics of pedestrians. Results. During the research, it was established that the level of comfort is characterized by a set of parameters: geometric dimensions of premises, intensity and speed of pedestrian flows, visual perception of space, and psychophysiological state of visitors. Based on the analysis, the use of a comfort index is proposed, which allows for a quantitative assessment of the conditions for movement in buildings. The model is effective in evaluating planning decisions and identifying areas of congestion. Scientific novelty. The scientific novelty lies in the improvement of existing methods for assessing the comfort level of transport buildings for pedestrians by introducing the concept of a comfort index, which includes the geometric parameters of premises, flow characteristics, and behavioral features of pedestrians of different categories. Practical relevance. The practical significance of the work lies in the possibility of applying the results obtained during the reconstruction and new construction of stations, improving the organization of pedestrian traffic in station buildings, taking into account comfort indicators.